2000
DOI: 10.1074/jbc.m003387200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a Large Chondroitin Sulfate/Dermatan Sulfate Proteoglycan, Versican, to L-selectin, P-selectin, and CD44

Abstract: Here we show that a large chondroitin sulfate proteoglycan, versican, derived from a renal adenocarcinoma cell line ACHN, binds L-selectin, P-selectin, and CD44. The binding was mediated by the interaction of the chondroitin sulfate (CS) chain of versican with the carbohydrate-binding domain of L-and P-selectin and CD44. The binding of versican to L-and P-selectin was inhibited by CS B, CS E, and heparan sulfate (HS) but not by any other glycosaminoglycans tested. On the other hand, the binding to CD44 was inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
194
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(207 citation statements)
references
References 61 publications
(65 reference statements)
8
194
0
4
Order By: Relevance
“…Taken together, studies have suggested that versican might enhance tumor behavior through interaction with hyaluronan and subsequent activation of CD44. Interestingly, studies have demonstrated that versican may interact directly with CD44 through its GAG chains, independent of hyaluronan [52]. It is important to know if this interaction also induces CD44 activation and transduces signals.…”
Section: Interaction Of Versican With Other Matrix Molecules Versicanmentioning
confidence: 99%
“…Taken together, studies have suggested that versican might enhance tumor behavior through interaction with hyaluronan and subsequent activation of CD44. Interestingly, studies have demonstrated that versican may interact directly with CD44 through its GAG chains, independent of hyaluronan [52]. It is important to know if this interaction also induces CD44 activation and transduces signals.…”
Section: Interaction Of Versican With Other Matrix Molecules Versicanmentioning
confidence: 99%
“…It has been reported that a large CS/DSPG interacts through its CS/DS chains with the adhesion molecules L-and P-selectin, CD44, and chemokines. Kawashima et al (1999Kawashima et al ( , 2000 and others (Capila and Linhardt, 2002;Hirose et al, 2001) reported that oversulfated CS/DS, containing [4)GlcA(β1-3)GalNAc4S6S (β1-] n sequences, interacts with L-selectin, P-selectin, and chemokines. Our findings may indicate that these same [4)GlcA(β1-3)GalNAc4S6S(β1-] n sequences in CS would be associated with the strongest effects on the promotion of the Th1-type cytokine production and the inhibition of the Th2-type cytokine production.…”
Section: A New Concept For Explaining the Effect Of Chondroitin Sumentioning
confidence: 99%
“…Regard-ing gliomas, a decrease of versican expression has been described in the extracellular matrix, whereas there is an up-regulation of versican in tumor vessels compared to normal cerebral vessels. 9 Because of its ability to interact with hyaluronate, 10 tenascin 11 and other proteins, and cytokines, [12][13][14][15] versican may contribute to the malignant properties of tumor cells. In this sense, it has been described that the versican-rich extracellular matrices exert an anti-adhesive effect on the cells, thus facilitating tumor cell migration and invasion.…”
mentioning
confidence: 99%